PENINGKATAN HASIL BELAJAR IPS SEJARAH MATERI LETAK DAN LUAS INDONESIA MENGGUNAKAN ALAT PERAGA PETA - Empat Patimah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This study aims to improve student learning outcomes in class VII B MTsN 1 Pangandaran in social studies subjects. Improved student learning outcomes by being given action through the use of maps as learning aids. This research uses Classroom Action Research which consists of two cycles. Each cycle consists Two meetings. Each Meating consist of four stages, namely planning, acting, observing and evaluating the results of the action and reflecting until the expected improvement. The population of this study were all students of class VII B MTsN 1 Pangandaran with 30 students. The results of the study indicate that the use of maps as learning aids can improve student achievement in social studies subjects. This is evidenced by an increase of 20% compared to pre-treatment. Learning achievement in the first cycle of the second meeting increased by 40% to 67% in the second cycle of the 1st meeting. Similarly, learning outcomes in the second cycle of the first meeting increased by 20% to 87% at the end of the second cycle of the second meeting. -learning is proven to be able to improve student learning outcomes on the concept of understanding the human environment using of maps as learning aids of the location and area of ​​Indonesia in class VII B MTsN 1 Pangandaran.